Addressing flood hazards via environmental humanities in Malaysia - Chan, Ngai Weng (Environmental Management Society, Malaysia, 2011)
Much of the environmental problems facing humanity in the 21st Century are human-created but society has chosen mostly to tackle them via the structural approach, employing science and technical solutions while ignoring the root causes. This structural approach has been used heavily to tackle flood hazards in Malaysia and is found to be ineffective. Since flood causes have their root causes in human society, clearly the most appropriate and effective way to address them is not through science but through tackling the human causes. The study of Environmental Humanities (EH) can provide more effective answers to not only flood but also environmental problems. EH relates to investigating environmental/sustainability issues from the perspective of the humanities. In the modern era, the humanities has been transformed into high-tech areas (as many researches in humanities now integrate the study and use of technology in environmental hazard studies). Consequently, the development of EH is increasingly permeating into all fields. This article examines how EH deals with flood management and the range of contemporary environmental problems resulting from the interactions between humans and nature. More significantly, although floods have evolved to become a common feature in the lives of a significant number of Malaysians, increased exposure and vulnerability were demonstrated to be largely influenced by human activities. Human forces such as socio-cultural, political, economy and institutional are probably more important than natural causes and they need to be researched. The answers to more effective floodplain management is expected to be found in the human dimension rather than the natural sphere. Thus, human contexts need to be identified and understood for more effective flood management. Finally, EH’s contribution is to aid understanding that flood problems are multi-causal phenomena, and to develop skills in humans necessary for effective environmental citizenship and leadership in the area of flood management.